Interaction Between Religious People in the Qur’an: Examining Tolerance in Tafsir Bun Yanun Marshush - Husna, Rifqatul; Maqfirah, Muflihatul; Alsounusi, Salih Abdulrahman (SUHUF, 2023)
Indonesia is a pluralistic and tolerant country with the largest Muslim population in the world. Various ethnicities, cultures, and religions thrive in Indonesia. This diversity is, on the one hand, a noble value, but on the other hand, it has led to conflicts among fellow citizens due to the misuse of the true meaning of tolerance. Therefore, it is crucial to have an understanding of the concept of tolerance along with its rules to create a harmonious and respectful coexistence among religious communities in Indonesia. This research was conducted to find out the meaning of tolerance according to Indonesian ulama who are active in crucial activities for religious relations in Indonesia by referring to the QS. Al-Mumlahanah in the interpretation of Bun-Yanun Marshush. The research employs a literature review using qualitative analysis techniques and a thematic (maudhui) method. Data collection is based on documentation techniques, where primary data is sourced from the Qur’an and the book “Tafsir Al-Qur’an Juz XXVIII Juz Qad Sami’ Allah Bun-Yanun Marshush” (A Solid Building). Secondary data is drawn from various relevant tafsir books, publications, and journals related to the subject, which are then comprehensively studied. In conclusion, this research finds that: 1) Allah does not prohibit Muslims from aiding non-Muslims with the condition that they do not act hostile towards and expel Muslims from their homeland, and 2) the prohibition forming friendships with those who assist non-Muslims in their hostility against Muslims, with a clear distinction between right and wrong